Utilizing the Fundamental Nd: YAG Laser for the Pulsed Laser Ablation Approach to Synthesize Zinc Oxide Nanoparticles - Shehab, Maryam M.; jebur, Eman K. (Iraqi Journal of Science, 2025)
High-purity Zinc Oxide nanoparticles (ZnO NPs) were successfully synthesized using the pulse laser ablation technique. Low-power neodymium-doped yttrium aluminum garnet (Nd: YAG) laser was utilized as the energy source for the present study. A surface of a high-purity (99.95%) zinc plate submerged in 10 milliliters of water was exposed to a pulse laser beam of wavelength (λ=1064 nm), (τ= 9 ns). ZnO NPs in colloidal form were effectively synthesized. The characteristics of the nanoparticles were investigated using (XRD, SEM, Zeta Potential, and PL) approaches. XRD patterns revealed the hexagonal wurtzite structure of the nanoparticles. Was detected by XRD. The spherical form of the generated nanoparticle was seen in the SEM images of ZnO NPs. The photoluminescence spectrum showed two peaks of emission: one referring to band gap excitonic emission at 392 nm, the other at 512 nm has to do with the existence of oxygen vacancies that are singly ionized.